The Principle Of Democracy And Participation In Making Village Regulations As An Effort To Develop A Just Village - Muhamad Sadi Is; Sobandi Sobandi; Khalisah Hayatuddin; Suharyono Suharyono; Jemmi Angga Saputra; Abdul Basir Bin Mohamad (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2023)
Overall, of course, development was carried out from the village, considering that as a country, Indonesia has thousands of villages, which must be carried out in a just development; of course, this development must be based on applicable laws, both laws on villages and village regulations, as the legal basis for carrying out this development. A good village regulation is certainly based on democratic principles and the principle of aspirations in making it. Normative legal research was used based on secondary data sources, especially the Law of the Republic of Indonesia Number 6 of 2014 on Villages, and analyzed qualitatively. The results of the study concluded that, first, good village regulations must contain the principles of democracy and aspirations in the process of making them so that they could produce village regulations in line with the mandate of the Pancasila and the 1945 Constitution of the Republic of Indonesia, and what was expected by the local village community, so that they could make a village as the main pillar for the progress of the Indonesian nation and state both in the present and the future. Second, A just village development must be based on village regulations to carry out development in villages, both village infrastructure development and village human resource development, as mandated in the Law of the Republic of Indonesia Number 6 of 2014 on Villages.